Failure of introduction of food allergens after negative oral food challenge tests in children - van der Valk, J. P. M. (Eur J Pediatr, 2015)
One of the purposes to perform an oral food challenge (FC) test is to avoid unnecessary elimination of food allergens. In case of a negative FC test result, the food can be introduced. It is, however, unknown if patients act according to the outcome of the test. This study evaluates the rate of introduction of peanut, hazelnut, cow’s milk or hen’s egg allergens after a negative FC test. We investigated the introduction rate of children (0–18 years) with a negative FC test visiting the Department of Allergology, Erasmus Medical Centre Rotterdam from 2008 till 2013 and the factors that influence the rate of introduction. Patients were asked to complete a comprehensive questionnaire about their FC test. In total, 157 (38 % girls, mean age during challenge 6.9 years) participated in the study. Of these FC tests, 104 (56 %) were followed by a successful introduction, 30 (16 %) by a partly introduction (traces or processed foods) and 52 (28 %) by a failed introduction. Peanut and hazelnut showed a statistically significant lower successful introduction rate. Age, gender, symptoms during FC test, dietary advice and time period to introduction significantly influenced the rate of introduction. One fourth of the children with failure of introducing foods experienced symptoms during the introduction. Conclusion: More than one quarter of all children with a negative FC test result did not introduce the food. The FC test in its current form does not achieve its objective for this group of children.